Iranian Intensive Care Unit Nurses\' Experience of Patient Safety Culture: A Qualitative Study - Samrand Fattah Ghazi; Mehrzad Mashayekhi; Parvaneh Asgari (نشریه پرستاری ایران)
Background & Aims Patient safety is one of the fundamental principles of health care. The investigation of patient safety culture is a step towards providing safe conditions for patient care. This study aims to explore the Iranian intensive care unit (ICU) nurses’ experiences of patient safety culture in hospitals. Materials & Methods This is a qualitative study using the conventional content analysis method. Participants were 18 ICU nurses from three hospitals affiliated to Tehran University of Medical Sciences in 2021-2022, who were selected using a purposive sampling method. In-depth semi-structured interviews was carried to collect data. Data were analyzed using Graneheim and Lundman’s content analysis method. Results Three themes were extracted: Individual (sufficient knowledge and skills, observance of professional values, work experience), interpersonal (inter-departmental communication, intra-departmental communication), and organizational (supportive management versus punitive response to errors, equipment safety, irrational workload, and employee empowerment). Conclusion The results revealed that the concept of patient safety culture in Iranian hospitals is multidimensional (individual, interpersonal, and organizational). Integrating effective patient safety culture into all parts of the organization should be the priority of hospital management programs. To promote awareness in the field of patient safety culture while holding regular training courses, hospital managers should encourage non-punitive responses to errors and teamwork to clarify the performance and expectations of the health system about improving patient safety.